Pengaruh Digital Skill, Transformational Leadership dan Readiness for Change sebagai Variabel Mediasi terhadap Innovative Work Behaviour - Haspemi, Yenof Patrione; Syahrul, Laura; Fahmy, Rahmi (SAFE-Network, 2023)
The decline in the Global Innovation Index (GII) in Indonesia highlights the importance of promoting Innovative Work Behavior. In response, the government has initiated a Large-scale Bureaucracy Reform Design, emphasizing the significance of innovation in achieving world-class governance. Innovative Work Behavior is defined as creative ideas and contributions from employees in solving job-related problems, which impact organizational performance improvement. This research is motivated by the need for innovation in the public sector, particularly in the digital transformation of government services. The purpose of this study is to analyze the influence of Digital Skills and Transformational Leadership on Innovative Work Behavior, mediated by Readiness for Change, in the context of implementing Dukcapil Go Digital in the Population and Civil Registration Office (Disdukcapil) of Dharmasraya Regency. This research is a case study with a quantitative approach. The research respondents are all employees of Disdukcapil Dharmasraya Regency. This study uses primary data obtained from respondent answers through a questionnaire filled out via Google Forms. Data analysis technique uses the SEM-PLS (Structural Equating Modeling-Partial Least Square) method. The research findings indicate that Digital Skills and Transformational Leadership have a positive and significant influence on the Innovative Work Behavior of employees in the Population and Civil Registration Office of Dharmasraya Regency. Digital Skills also have a positive and significant influence on Readiness for Change, while Transformational Leadership does not have a significant influence on Readiness for Change. Although Readiness for Change has a positive impact, it is not significant on Innovative Work Behavior. Furthermore, Readiness for Change is not able to function as a mediator between Digital Skills and Innovative Work Behavior, as well as between Transformational Leadership and Innovative Work Behavior.